ANALYSIS OF THE RATES OF ECONOMIC GROWTH IN THE CITY OF SAINT PETERSBURG: INDUSTRY STRUCTURE AND DYNAMICS - Andrei V. Agashin; Vladimir S. Urazgaliev (Модели, системы, сети в экономике, технике, природе и обществе, 2023)
Background. The economic growth of Saint Petersburg is the result of an increase in labor productivity and the share of high-tech and knowledge-intensive industries in the gross regional product (up to 45 % by 2035), the development of priority industries in the region, as well as the use of various tools to stimulate socio-economic growth. In previous years, there has been a trend towards a slowdown in economic growth in Saint Petersburg, which may indicate the failure to achieve the goals and objectives stated in the strategic documents, as well as the inefficiency of the applied tools for the development of the city. The purpose of this work is to study the dynamics of the gross regional product of Saint Petersburg in order to identify existing trends in its dynamics. Materials and methods. During the study, the dynamics of the GRP of Saint Petersburg for the period 1998–2020 was analyzed. using various statistical techniques and methods, including regression analysis and the hypothesis of time series stationarity (ADF-test) of the dynamics of GRP and GRP per capita in Saint Petersburg, the rating of regions was used to determine the place of Saint Petersburg among the regions of the Russian Federation in terms of the standard of living of the population (GRP and GRP per capita). The methodological basis of the study was general scientific (synthesis, induction, deduction) and special methods of economic analysis (logical and statistical analysis), the work presents the methodology of system analysis, and also uses a comparative method when comparing regional ratings by economic growth, applied econometric methods for analyzing stationarity dynamics of the gross regional product of Saint Petersburg. Results. Economic growth rates in 1998–2020 tended to decrease, there was a noticeable decrease in the positions of Saint Petersburg in the ranking of regions in terms of GRP per capita, economic growth rates are lower than in the Forecast for the socio-economic development of Saint Petersburg until 2035, which indicates insufficiently effective stimulation of the socio-economic development of the region. Conclusions. It is necessary to search foIt is necessary to search for new growth points for the region's economy and their subsequent stimulation, the implementation of a structural economic policy with an emphasis on the development of high-tech and knowledge-intensive industries, which in the future can contribute to achieving high sustainable economic growth rates of at least 5 % annually.r new growth points for the region's economy and their subsequent stimulation, the implementation of a structural economic policy with an emphasis on the development of high-tech and knowledge-intensive industries, which in the future can contribute to achieving high sustainable economic growth rates of at least 5 % annually.